Association between subjective hearing difficulty and cognitive impairment among community-dwelling older adults: A secondary analysis of the 2023 National Survey of Older Koreans - Dukyoo Jung; Sukyung Byeon; Soogyung Shin; Leeho Yoo; Hyein Seo (Journal of Korean Gerontological Nursing, 2026)
Purpose: Age-related hearing loss (ARHL) is a significant public health concern affecting older adults’ health. Although its association with cognitive impairment is increasingly recognized, evidence among South Korean older adults remains limited. This study examined the association between subjective hearing difficulty and cognitive impairment and factors associated with cognitive impairment according to subjective hearing difficulty status. Methods: This secondary analysis used data from the 2023 National Survey of Older Koreans, including 7,419 participants. The main variables were subjective hearing difficulty and cognitive impairment; complex-sample multivariable logistic regression analyses were conducted. Results: Of the 7,419 participants, 20.1% reported subjective hearing difficulty. Among these, only 13.1% had been diagnosed with ARHL and 26.3% used hearing aids. Subjective hearing difficulty was associated with higher odds of cognitive impairment (odds ratio [OR]=1.50, 95% confidence interval [CI]=1.26~1.80, p